RELATIONSHIP OF SIEVING GRAIN SIZE FRACTION WITH MACERAL COMPOSITION AND QUALITY FOR COAL SEAM A1 BANKO BARAT - Alfianita, Lia
The increase in world energy consumption has resulted in higher demand for and production of coal. During the coal production process, grain size variations occur. The condition is caused by variable and unevenly distributed grain size distribution, which can cause problems in coal quality analysis. This study aims to determine the effect of grain size fraction of sieving results on a laboratory scale on mineral composition and proximate analysis during preparation. This study used the channel sampling method to take three samples from coal seam A1 Banko Barat at two-meter intervals. Then the three samples were divided into six-grain size fraction from a coarse fraction (+5#) to a fine fraction (-230#). The results show a significant effect of grain size fraction on the maceral composition and proximate analysis. When the grain size gets finer, the composition of huminite maceral tends to increase, while liptinite tends to decrease, and inertinite shows no trend. This condition also affects the content of fixed carbon, inherent moisture, and volatile matter tends to decrease, while the ash content tends to increase as the grain size decreases. Thus, the grain size fraction strongly influences the maceral enrichment composition and quality. Differences in the physical and chemical properties of coal constituents cause this condition. Changes in each fraction’s maceral composition and proximate analysis indicate that coal has heterogeneous properties. Therefore, when sampling coal, one must pay attention to the grain size fraction to avoid errors in interpretation.